Meningkatkan Kepercayaan Diri Siswa Melalui Ekstrakurikuler Tari Di SDIT Tiara Az-Zahra Palangka Raya - Annisa, Dea Rizky; Mahmudah, Istiyati (Universitas Tanjungpura, 2024)
Self-confidence is included in the social-emotional aspects that have an important role in shaping students' identity and personal development, especially in elementary school students. However, there are still schools that only focus on cognitive aspects and tend to pay less attention to other aspects such as skills, attitudes and social-emotional aspects. Extracurricular dance refers to activities outside of school hours to express feelings through beautiful body movements. This study aims to describe whether extracurricular dance can increase students' self-confidence. This research uses a qualitative approach with a descriptive type. The data collection techniques are through observation, interviews, documentation, and also questionnaires. The data analysis technique goes through several stages including collecting data, reducing data, and presenting conclusions. The research subjects here are students who take part in extracurricular dance. The location or place of research is at Tiara Az-Zahra Palangka Raya Integrated Islamic Elementary School. While the research time was on Wednesday, March 6, 2024. The results showed that through extracurricular dance at school can increase students' self-confidence which is realized by students wanting to perform dance in front of many people.